The Correlation Tourist Attraction with Revisit Intention of Agritourism Pelaga Badung Bali, Indonesia - I Gusti Bagus Rai Utama; Christimulia Purnama Trimurti (Petra International Journal of Business Studies, 2019)
The Pelaga Agritourism area is dominantly visited by students, who are predominantly less than 20 years old, some of them are from the age group of 21 to 40 years. They are predominantly come from around the City of Denpasar and Badung Regency. They are interested in visiting Pelaga because a unique village tourist attraction, views of gardens and farmland, natural beauty, the beauty of the park, cultural friendly and environmentally friendly tourist attractions, public facilities, telecommunications, restaurants and centers the agriproduct market, the people who are friendly to tourist arrivals, easy to reach locations, the availability of transportation to the location, and the proximity to the city center. Dominant tourists willing to re-visit Pelaga significantly influenced by the unique village tourist attraction, views of the expanse of gardens or farmland, natural beauty, the beauty of the park, and the ease of reaching the Pelaga location from their residence.